(х-4)(4х+6)=(х-5)^2 p.s. ^-это степень

Айгуль11111катон Айгуль11111катон    3   28.03.2019 19:40    0

Ответы
NinjaKiller1337 NinjaKiller1337  27.05.2020 04:02

4x^2+6x-16X-24=x^2-10x+25

4x^2-x^2+6x-16x+10x-24-25=0

3x^2-49=0

3x^2=49 перенесли в противоположную сторону меняя знак

3x^2=49

x^2=49/3

x^2=16,3

x1=корень из 16,3

х2=минус корень из 16,3

 

ПОКАЗАТЬ ОТВЕТЫ
kamallm712oxbgkk kamallm712oxbgkk  27.05.2020 04:02

4x^2+6x-16X-24=x^2-10x+25

4x^2-x^2+6x-16x+10x-24-25=0

3x^2=49 

x^2=49/3

x^2=16,3

x1=корень из 16,3

х2=минус корень из 16,3

ПОКАЗАТЬ ОТВЕТЫ